2004
DOI: 10.1007/bf03033223
|View full text |Cite
|
Sign up to set email alerts
|

Role of endocannabinoid system in mental diseases

Abstract: In the last decade, a large number of studies using Delta9-tetrahydrocannabinol (THC), the main active principle derivative of the marijuana plant, or cannabinoid synthetic derivatives have substantially contributed to advance the understanding of the pharmacology and neurobiological mechanisms produced by cannabinoid receptor activation. Cannabis has been historically used to relieve some of the symptoms associated with central nervous system disorders. Nowadays, there are anecdotal evidences for the use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 108 publications
(118 reference statements)
2
35
0
3
Order By: Relevance
“…Dysfunction of this system is thought to be involved in the development of affective disorders such as anxiety and depression. Cannabinoid receptors have been implicated in the regulation of anxiety-like behaviors (Berrendero and Maldonado, 2002;Chaperon and Thiebot, 1999;Degenhardt et al, 2001;Manzanares et al, 2004). For example, cannabinoid administration causes both anxiogenic and anxiolytic responses in animal studies (Rodriguez de Fonseca, Rubio et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of this system is thought to be involved in the development of affective disorders such as anxiety and depression. Cannabinoid receptors have been implicated in the regulation of anxiety-like behaviors (Berrendero and Maldonado, 2002;Chaperon and Thiebot, 1999;Degenhardt et al, 2001;Manzanares et al, 2004). For example, cannabinoid administration causes both anxiogenic and anxiolytic responses in animal studies (Rodriguez de Fonseca, Rubio et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term cannabis use has also been related to several affective disorders including anxiety, depression, cognitive impairment, and psychosis (Troisi, Pasini et al 1998;Arnold, Topple et al 2001;Degenhardt, Hall et al 2001;Berrendero and Maldonado 2002;Manzanares, Uriguen et al 2004). One longitudinal study reported that daily use of cannabis by teenagers was associated with a two-fold increased risk for depression and anxiety during their adult years (Patton, Coffey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated administration of cannabinoid agonists has been associated with activation of the stress-response system, anxiety, depression, and cognitive impairment (Arendt and MunkJorgensen 2004;Arnold et al 2001;Berrendero and Maldonado 2002;Degenhardt et al 2001;Manzanares et al 2004;Troisi et al 1998). The neural substrates underlying these effects remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…19 Thus, cannabinoids, which are the main component of marijuana, act with exocannabinoids on the endocannabinoid system, which plays a significant role in vulnerability to development of addiction and other mental disturbances. 20 CNR2 may also be associated with addiction vulnerability as a modulator of the reward system. CNR2 has been observed in the brainstem, 21 cerebellum 22 and several other regions of the brain.…”
Section: Introductionmentioning
confidence: 99%